De ombligo a ombligo: Notes on Embodiment and Translation - Borrero, Juliana; Epp, Ellie (Tusaaji: A Translation Review, 2014)
A translation of the poem What will we know by Ellie Epp, translated by Juliana Borrero, with notes by the author and the translator.